2010
DOI: 10.3389/fnsys.2010.00031
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Superficial and deep laminar domains of activity in the visual cortex during rest and stimulation

Abstract: Spatial patterns of spontaneous neural activity at rest have previously been associated with specific networks in the brain, including those pertaining to the functional architecture of the primary visual cortex (V1). However, despite the prominent anatomical differences between cortical layers, little is known about the laminar pattern of spontaneous activity in V1. We address this topic by investigating the amplitude and coherence of ongoing local field potential (LFP) signals measured from different layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
262
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(299 citation statements)
references
References 57 publications
(66 reference statements)
35
262
1
1
Order By: Relevance
“…The α-power was strongest in layers 5/6 (t test, n = 24 penetrations, all Ps < 0.001) with a secondary peak in layer 1/2 (layers 1/2 higher than layers 3 and 4; t test, P < 0.001) (Fig. 2 F and G) as has been observed previously (13,39). In contrast, γ-power was stronger in layer 3 than in the other layers (Fig.…”
Section: Significancementioning
confidence: 50%
See 1 more Smart Citation
“…The α-power was strongest in layers 5/6 (t test, n = 24 penetrations, all Ps < 0.001) with a secondary peak in layer 1/2 (layers 1/2 higher than layers 3 and 4; t test, P < 0.001) (Fig. 2 F and G) as has been observed previously (13,39). In contrast, γ-power was stronger in layer 3 than in the other layers (Fig.…”
Section: Significancementioning
confidence: 50%
“…In contrast, γ-power was stronger in layer 3 than in the other layers (Fig. 2 F and G) (t-test, all Ps < 0.001) (39,40). The laminar pattern of LFP power was similar, irrespective of whether the RF fell on figure or ground (Fig.…”
Section: Significancementioning
confidence: 95%
“…The cat visual cortex also contains a class of pyramidal and stellate cells termed "chattering cells," which are localized to layers 2/3 and fire with high-frequency bursts in the gamma-frequency range (32,33). A recent study in awake monkeys using translaminar electrodes also reported a predominance of gamma activity in the LFP of superficial layers in area V1 (34).…”
Section: Discussionmentioning
confidence: 95%
“…The laminar structure of the visual cortex has been known for a long time, yet whether there are differences in the way in which neuronal populations across cortical layers encode information is just beginning to be understood (3,4,43). Aside from a study in anesthetized cat V1 (32) reporting pronounced adaptive effects irrespective of cortical depth, whether adaptation influences sensory coding in a layer-specific manner has never been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical layers are ubiquitous structures throughout neocortex (1, 2) that consist of highly recurrent local networks that communicate among each other to possibly influence the information encoded in population activity. In recent years, significant progress has been made in our understanding of the differences in response properties of neurons across cortical layers (3,4), yet there is still a great deal to learn about whether and how neuronal populations encode information in a layerspecific manner. A measure of the activity of a local population (or ensemble) of neurons (5) is captured by local field potentials (LFPs), which are composed of low-frequency extracellular voltage fluctuations, including local excitatory and inhibitory intracortical inputs (6) believed to originate from within 250-500 μm of the recording site (7,8).…”
mentioning
confidence: 99%